The effects of message strategy and execution framework on teenage boy's processing of print advertisements in India - Tuhin Chattopadhyay (International Journal of Business Science & Applied Management (IJBSAM), 2010)
The purpose of this paper is to explore the most effective print advertising strategy in terms of message strategy and execution framework for teenage boys in India. Teenage boys (n = 400) watched twenty advertisements in which message strategy and execution framework were manipulated in a 2x10 completely crossed factorial design and were asked to rate their attention, comprehension, retention, attitudes and purchase motivation about these advertisements. Results suggest that affective message strategy along with personality symbol as execution framework is most effective for teenage boys. Findings are then discussed.
Keywords: 650; print advertising; information processing; message strategy; execution framework; teenage boys